Analysis Relationship Family Support and Health Cadre with Elderly Hypertension Practice in Controlling Health at Primary Health Care Mranggen Demak - Irani, Ninin (University of Muhammadiyah Semarang, 2019)
Hypertension is a major risk factor for cardiovascular disease which is the leading cause of death in Indonesia. Data Research Department of Health in 2005, showed hypertension and cardiovascular disease is still quite high and even tends to increase with the lifestyle that much of the behavior of healthy and clean life, high cost of treatment of hypertension, erroneous perception of the public accompanied by a lack of safety facilities hypertension , Hypertension is actually a disease that can be prevented if the risk factors can be controlled and healthy behaviors (healthy behavior) which practices or activities related to efforts to maintain, control and improve health. Data from Demak district health department, the incidence of hypertension has increased within the last three years. The aim of this study was to determine the relationship of family support and cadres with elderly Hypertension practices in controlling health in Puskesmas Mranggen, Demak by using a cross-sectional study with a quantitative approach. The sample size for a quantitative approach is 285 respondents (total sampling). The data were analyzed using univariate, bivariate with chi-square. The results showed an association between family support for elderly people who suffer from hypertension with the practice of elderly hypertension in controlling health (p = 0.048), there is a relationship between support for health workers to the elderly who suffer from hypertension with Practice elderly hypertension in controlling health (p = 0.049). Advice to the puskesmas officers in order to improve the quality of health care, home visits, provide health education particularly on controlling health benefits for elderly hypertension and cross-sectoral cooperation in the implementation of an integrated program of coaching post (posbindu) elderly.